1261 Neurodevelopmental Outcome in Extremely Premature Infants Born in Switzerland Between 2000–2008, Preliminary Data of the Swiss Neonatal Network. (October 2012) - Schlapbach, LJ; Adams, M; Aebischer, M; Latal, B; Grunt, S; Borradori-Tolsa, C; Bickle-Graz, M; Bucher, HU; Natalucci, G
Abstract : Introduction: So far, national outcome data on extremely premature infants in Switzerland were not available, and discussions on the care of these patients were based on earlier studies from other countries. This national study assessed neurodevelopment in Swiss infants born between 2000 and 2008 at 24 0/7 to 27 6/7 weeks gestational age. Methods: Neurodevelopment was assessed at 2 years using the BSID II. Moderate neurodevelopmental disability (ND) was defined as a mental (MDI) or psychomotor (PDI) development index of 55–70, or mild cerebral palsy (GMFCS level 2). Severe ND was defined as a MDI or PDI < 55, cerebral palsy (GMFCS level ≥3), deafness or blindness. Multivariate logistic regression was performed. Results: Among the 1147 extremely preterms born during the study period 303 (26%) died. Follow-up information was available in 684 (81%) survivors. 440 (64%) showed normal development, 166 (24%) moderate ND, and 78 (12%) severe ND. Severe ND was significantly (p<0.05) associated with earlier year of birth, major intracerebral lesions, bronchopulmonary dysplasia, grade 3 retinopathy of prematurity, and lower socioeconomic status. In contrast, birth weight, gestational age and sex showed only trendwise associations with severe ND. Conclusion: Based on these preliminary analyses, we now are ready to establish representative Swiss national data on the outcome of extremely premature infants. These will offer guidance to obstetricians, neonatologists, neurologists and parents based on Swiss data.